HUBUNGAN POWER OTOT LENGAN DAN BAHU DENGAN KECEPATAN PUKULAN DEPAN PADA ATLET PENCAK SILAT PERSAUDARAAN SETIA HATI TERATE PEKANBARU - Sakaria Sakaria; Ramadi Ramadi; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study was to determine the relationship of arm and shoulder muscle power with the speed of the front stroke on the Setia Hati Terate Pencak Silat athlete in Pekanbaru. This research was conducted in the Field of Training in the Pencak Silat Setia Hati Terate in Pekanbaru. Conducted in November 2019 - April 2020. This research is included in the type of correlational research (Correlation Research) which involves collecting data to determine whether there is a relationship and the level of relationship between two or more variables. This study uses a total sampling technique (saturated sample), where the entire population used as a sample is as many as 8 people. From the results of the research that has been done, it can be concluded that there is a very strong relationship together between the arm and shoulder muscle power to the speed of the front punch of the Setia Hati Terate Pencak Silat athlete in Pekanbaru, where rtable at a significant level (0.05) = 0.707 means r count (0.730)> r table (0.707), which means it contributes normally.Key Words: Jump Rope Training, Slowly, Endurance Tennis Team